Development and Types of Passive Samplers for Monitoring Atmospheric NO2 and NH3 Concentrations. (2001) - Tang, Y.S.; Cape, J.N.; Sutton, M.A.
Abstract : Numerous passive samplers based on the 'Palmes-tube' have been developed for ambient air monitoring. In each case, the diffusion path length and/or crosssectional area are modified to achieve the desired sampling rate. 'Tube-type' samplers are low sensitivity samplers suitable for long-term monitoring, whereas the 'badge-type' samplers have faster sampling rates suited to short-term monitoring. In the U.K., diffusion tubes are widely used for monitoring nitrogen dioxide (NO2) and ammonia (NH3). The open-ended diffusion tubes are prone to positive bias caused by incursion of wind eddies, leading to a shortening of the diffusion path. By using a porous membrane at the inlet, wind incursion is prevented, but an additional diffusion resistance is imposed and it is necessary to calibrate the tubes against a reference method to obtain an effective sampling rate. For NO2 sampling, positive bias also arises from the reaction of NO with O3 within the sampler. The interference from the chemical reaction is severe close to NO sources, with errors up to 30% for curbside locations when using the 'tubetype' sampler. In rural areas, where NO concentrations are small relative to NO2, these errors are small. In some implementations, there is also a negative bias over long sampling periods caused by the degradation of trapped NO2. The low sampling rates of diffusion tubes make them too uncertain for use at background NH3 concentrations (<1 μg NH3 m-3) where they significantly overestimate concentrations. Badge-type samplers such as the 'Willems badge' samplers permit accurate sampling at low ambient NH3 concentrations, but suffer from saturation at high concentrations and sensitivity to wind speed. A passive sampler optimised for monthly measurements of NH3 is reported here, together with its application in the U.K. National Ammonia Monitoring Network.